2022
DOI: 10.1371/journal.pone.0272573
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year in-hospital mortality trends among Japanese injured patients by age, injury severity, injury mechanism, and injury region: A nationwide observational study

Abstract: The Injury Severity Score (ISS) is widely used in trauma research worldwide. An ISS cutoff value of ≥16 is frequently used as the definition of severe injury in Japan. The mortality of patients with ISS ≥16 has decreased in recent years, owing to the developing the trauma care system. This study aimed to analyze the prevalence, in-hospital mortality, and odds ratio (OR) for mortality in Japanese injured patients by age, injury mechanism, injury region, and injury severity over 10 years. This study used the Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This was much higher than that in other countries, with a median age of 30 years in Sweden and a mean age of 31 years in London and 39 years in Germany 10–12. Previous reports have shown that there were differences in the medical resources available for the trauma care and mortality risk according to age, mechanism, injury region and injury severity 6 7 10–13. Therefore, it may be effective to focus on these mechanism-specific and age-specific characteristics and outcomes of patients with penetrating injury in order to establish a trauma care system suitable for Japanese patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This was much higher than that in other countries, with a median age of 30 years in Sweden and a mean age of 31 years in London and 39 years in Germany 10–12. Previous reports have shown that there were differences in the medical resources available for the trauma care and mortality risk according to age, mechanism, injury region and injury severity 6 7 10–13. Therefore, it may be effective to focus on these mechanism-specific and age-specific characteristics and outcomes of patients with penetrating injury in order to establish a trauma care system suitable for Japanese patients.…”
Section: Discussionmentioning
confidence: 93%
“…Several nationwide cohort studies have reported that the mortality rate and risk of patients with severe injuries vary according to age, injury mechanism and/or injury severity 1–3 5–7. Injured patients with older age, penetrating injury and/or a higher Injury Severity Score (ISS) have a higher mortality risk 6 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 10-year review of child injuries in Australia revealed that having a head injury and greater injury severity were associated with higher mortality rates [13]. In Japan, a report using the JTDB examined in-hospital mortality trends among injured patients between 2009 and 2018 [14]. The report suggested a significant decrease in mortality for the age group for the ages of 0-4 and 5-14 years [14].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical routine, a full-body CT scan is recommended and performed as a standard of care when potentially life-threatening injuries are suspected [1][2][3][4][5][6]. Abdominal trauma, which is often present among severely injured patients, can lead to such life-threatening conditions that need immediate surgical intervention [6][7][8]. A traumatic injury to the diaphragm (TID) is a potentially challenging condition that is often accompanied by other thoracoabdominal injuries [9][10][11].…”
Section: Introductionmentioning
confidence: 99%